Gender and the Allocation of Adult Time : Evidence from the Peru LSMS Panel Data - Ilahi, Nadeem (World Bank, Washington, DC, 2014)
Ilahi analyzes the determinants of intra-household time use in Peru in 1994 and 1997. She tests whether sickness, unemployment, the provision of water and energy services, and other factors affect the time use of men and women differently. The results show that women work up to a fifth more than men do and that women in poor households work more than those in rich ones, while there is no difference for men. Women's work is concentrated in housework and men's in income-generating activities. Sickness does not affect the work burdens of men or women, but it alters the composition: men work more in income-generating activities, and women tend the sick. Men bear a greater burden from female unemployment than do women from male unemployment. Improvements in the provision of water and energy services affect the time use of both men and women. And finally, demographic and life-cycle variables are as important as gender in explaining differences in time use.